Wasatiyyah-Based Religious Character Formation Model: An Implementation Study of Religious Moderation Values at MTs Generasi Teladan, Tabanan, Bali - Kholil Kholil; Benny Prasetiya; Muhammad Alfi Syahrin (Green Publisher, 2026)
Religious education in madrasahs remains predominantly characterized by normative and ritualistic approaches, limiting its effectiveness in fostering moderate, inclusive, and socially responsive religious character. Existing studies on religious moderation tend to be programmatic and fragmented, leaving a significant gap in understanding how wasatiyah values are systematically institutionalized as a character education model within the entire madrasah ecosystem. This study aims to analyze the model of wasatiyah-based religious character formation and to examine the effectiveness of its implementation on students’ religious and social behavior at MTs Generasi Teladan Tabanan, Bali. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis, and were thematically analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that wasatiyah values are integratively embedded through institutional policies, curriculum design, dialogical pedagogical practices, school culture, student development programs, restorative counseling services, and school–family collaboration. The effectiveness of implementation is reflected in the strengthening of disciplined yet non-extreme religiosity, emotional self-regulation, non-judgmental attitudes, and enhanced social competencies such as tolerance, empathy, and the ability to coexist harmoniously within a pluralistic context. The novelty of this study lies in conceptualizing wasatiyah-based religious character education as an operational and sustainable value system within multicultural madrasah settings.